A comparison of pre-millennium eruption (946 CE) and modern temperatures from tree rings in Changbai Mountain, Northeast Asia - H. Du; M. C. Stambaugh; J. J. Camarero; M.-H. Li; M.-H. Li; D. Yu; S. Zong; H. S. He; Z. Wu (Climate of the Past, 2023)
High-resolution temperature reconstructions in the previous millennium are limited in Northeast Asia, but they are important for assessing regional climate dynamics. Here, we present, for the first time, a 202-year reliable reconstruction of April temperature changes before the millennium volcanic eruption in 946 CE using tree rings of carbonized logs buried in the tephra in Changbai Mountain, Northeast Asia. The reconstructed temperature changes were consistent with previous reconstructions in China and the Northern Hemisphere. The influences of large-scale oscillations (e.g. El Niño–Southern Oscillation, ENSO) on temperature variability were not significantly different between the periods of 745–946 CE preceding the eruption and 1883–2012. However, compared to the palaeotemperature of the previous millennium, the temperature changes were more complex with stronger temperature fluctuations, more frequent temperature abruption, and a weaker periodicity of temperature variance during the last 130 years. These recent changes correspond to long-term anthropogenic influences on regional climate.